Fertility Augmentation of Non-Descript Delayed Pubertal Cattle Heifers through Mineral Mixture Supplementation and Hormonal Intervention - Chandra Adarsh, Vipin; Singh Rajoria, Jitendra; Pratap Sing, Abhiyuday; Kumar Ojha, Brijesh; Kumar Singh, Anil; Raje, Archana; Tomar, Priyanshu; Swaroop Peepar, Shishant (Animal Reproduction Update, 2023)
Normal productive and reproductive behavior in domestic animal is closely associated with interaction between hormonal and nutritional status of the animal system. Twenty-four non-descript delayed pubertal cattle of Rewa district, aged between 3-5 years were used to study the effect of dietary mineral mixture supplementation and double PG protocol on reproductive performance. Cows were randomly allocated into four equal groups (A, B, C & D), comprising three treatment groups (n=6), and control (n=6) group. Control group was fed ration containing same CP and energy level according to the body weight. Group A (n=6) was fed ration containing 0% mineral mixture feeding in total per day. Group B (n=6) was fed ration containing mineral mixture 1 % of ration feeding in total per day diet. Group C (n=6) were subjected for double PG protocol and GnRH. Group D (n=6) was fed ration containing mineral mixture 1 % of ration  and  double PG protocol and GnRH. Group D has slightly more progesterone levels comparison to group C because of pregnancy in more cows. Plasma progesterone concentration of B, C and D Group, which supplemented with mineral mixture and hormonal protocol were significantly high. At 60-day Group A and C has similar values of progesterone. Group D has low Estrogen values due to more number or non-cyclic cows then other groups. Mineral concentrations were also significantly high in treatment groups comparatively. Pregnancy rate obtained in non-descript delayed pubertal heifers after artificial insemination was recorded as 83.33% in Group D, while it was 100% in all other three groups. Estrus submission rate is 33.33%, 50.00%, 66.66% and 83.33 % in all four groups, respectively. Accordingly reproductive efficiency calculated in experimental groups is 33.33, 50.00, 66.66 and 69.44, respectively. Combination of hormonal protocol with mineral mixture supplementation showed comparatively better result with respect to submission rate and reproductive efficiency.
Keywords: Estrus induction; Fertility; Heifers; Hormone; Mineral supplementation